(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Phosphorus is an essential, but often unavailable nutrient for plant growth in the soil due to its low solubility. Phosphorus solubilizing bacteria (PSB) convert insoluble forms of phosphorus into soluble forms that can be taken up by plants. The study aimed to isolate and characterize PSB from the rhizosphere of millet plants in Lafia, and to evaluate their potential for improving soil fertility and crop productivity. Soil samples were collected from four different locations and plated on Pikovskaya’s agar medium. PSB colonies were identified based on their ability to produce clear zones around them. The PSB isolates were further characterized by morphological, biochemical, and molecular methods. The phosphate solubilizing activity and plant growth-promoting traits of the PSB isolates were also assessed. The PSB isolates were tested for their effect on the growth of millet seedlings in pots. The results showed that 16 PSB isolates belonging to four genera (Bacillus, Pseudomonas, Enterobacter, and Klebsiella) were obtained from the soil samples. The PSB isolates exhibited varying degrees of phosphate solubilizing activity, ranging from 11.2 to 81.6 mg/L. The PSB isolates also showed positive results for the production of indole acetic acid, ammonia, hydrogen-cyanide, and siderophore. The PSB inoculation significantly increased the shoot and root lengths, and fresh and dry weight of the millet seedlings. The study concluded that the PSB isolates from the millet rhizosphere in Lafia could enhance soil phosphorus availability and millet growth. The study recommended further research on the field application and optimization of the PSB inoculation.